1995
DOI: 10.1104/pp.108.3.949
|View full text |Cite
|
Sign up to set email alerts
|

Primary Metabolism in Plant Defense (Regulation of a Bean Malic Enzyme Gene Promoter in Transgenic Tobacco by Developmental and Environmental Cues)

Abstract: NADP-dependent malic enzyme (NADP-ME, EC 1.1.1.40) catalyzes the oxidative decarboxylation of malate to pyruvate, producing CO, and NADPH. We have examined regulatory properties of a 2.8-kb promoter-leader fragment of a bean (Pbaseolus vurgaris 1.) NADP-ME gene (PvME1) predicted to encode a cytosolic form of the enzyme by expression analysis of promoter-P-glucuronidase fusions in transgenic tobacco plants. l h e PvMEl promoter directed strong expression in stems, which was confined to vascular and pith tissues… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
56
0
2

Year Published

2001
2001
2023
2023

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 94 publications
(58 citation statements)
references
References 48 publications
0
56
0
2
Order By: Relevance
“…It has been known for quite a while that NADP-ME is induced in various abiotic stress conditions (Maurino et al, 2001;Liu et al, 2007) and during elicitor treatment and plant-pathogen interactions (Walter et al, 1988;Schaaf et al, 1995;Casati et al, 1997Casati et al, , 1999Maurino et al, 2001;Parker et al, 2009) and recently it was shown that NADP-ME induction proceeds more rapidly in incompatible compared with compatible interactions with B. distachyon (Parker et al, 2009). Consequently, the sites of NADP-ME induction and ROS production coincided during early infection with this hemibiotrophic fungus (Parker et al, 2009).…”
Section: Nadp-me2 Is Involved In Basal Defence In a Thalianamentioning
confidence: 99%
See 1 more Smart Citation
“…It has been known for quite a while that NADP-ME is induced in various abiotic stress conditions (Maurino et al, 2001;Liu et al, 2007) and during elicitor treatment and plant-pathogen interactions (Walter et al, 1988;Schaaf et al, 1995;Casati et al, 1997Casati et al, , 1999Maurino et al, 2001;Parker et al, 2009) and recently it was shown that NADP-ME induction proceeds more rapidly in incompatible compared with compatible interactions with B. distachyon (Parker et al, 2009). Consequently, the sites of NADP-ME induction and ROS production coincided during early infection with this hemibiotrophic fungus (Parker et al, 2009).…”
Section: Nadp-me2 Is Involved In Basal Defence In a Thalianamentioning
confidence: 99%
“…It has also been long speculated that nonphotosynthetic NADP-MEs would be involved in defence responses. It was shown that transcription of an NADP-ME gene in bean (Phaseolus vulgaris) was rapidly and transiently activated by fungal elicitor treatment in cell-suspension cultures (Walter et al, 1988) and that wounding caused a marked induction of NADP-ME promoter activity, which was also strongly induced upon application of stimuli related to pathogen defence, for example, reduced glutathione, fungal elicitor, cellulase and NADPH (Schaaf et al, 1995). NADP-ME was also shown to respond to plant defence elicitors in bean (Walter et al, 1994), wheat (Triticum aestivum; Casati et al, 1997) and maize (Zea mays; Maurino et al, 2001).…”
Section: Introductionmentioning
confidence: 99%
“…Plastidic nonphotosynthetic isoforms were suggested to be involved in plant defense responses (Casati et al, 1999) and in lipid biosynthesis by providing carbon skeletons and reducing power (Smith et al, 1992;Eastmond et al, 1997). Cytosolic isoforms have also been linked to plant defense responses (Schaaf et al, 1995) and, in addition, to lignin biosynthesis by providing NADPH (Schaaf et al, 1995) and to control the cytosolic pH by balancing the synthesis and degradation of malate (Martinoia and Rentsch, 1994). Another suggested role for the NADP-ME is the control of stomatal closure by degrading malate during the day (Outlaw et al, 1981;Laporte et al, 2002).…”
mentioning
confidence: 99%
“…This metabolic pathway was speculated to be involved as energy source for plant defense through the generation of pyruvate and NADPH (Casati et al 1999;Schaaf et al 1995). The NADP-ME is widely distributed among all types of plants.…”
Section: Discussionmentioning
confidence: 99%